Digital guided self-help for eating disorders: thematic analysis of participant text messages to coaches. Issue 2 (4th March 2023) - Sadeh-Sharvit, Shiri; Idan, Orly; Fowler, Lauren A.; Fitzsimmons-Craft, Ellen E.; Firebaugh, Marie-Laure; Smith, Arielle; Graham, Andrea K.; Goel, Neha J.; Flatt, Rachael E.; Balantekin, Katherine N.; Monterubio, Grace E.; Karam, Anna M.; et al.
ABSTRACT: Digital guided self-help for eating disorders (GSH-ED) can reduce treatment disparities. Understanding program participants' interests throughout the program can help adapt programs to the service users' needs. Participants were 383 college students receiving a digital GSH-ED, who were each assigned a coach to help them better utilize the intervention through text correspondence. A thematic and affective analysis of the texts participants had sent found they primarily focused on: strategies for changing their ED-related cognitions, behaviors, and relationships; describing symptoms without expressing an active endeavor to change; and participants' relationship with their coach. Most texts also expressed affect, demonstrating emotional engagement with the intervention. Findings suggest that participants in GSH-ED demonstrate high involvement with the intervention, and discuss topics that are similar to those reported in clinician-facilitated interventions. The themes discussed by digital program participants can inform future iterations of GSH-ED, thereby increasing scalability and accessibility of digital evidence-based ED interventions.